Interreligious dialogue and socio-religious dialogue in today's society - Petrov, George Daniel; Pleșa, Victor Marius (Technium Social Sciences Journal, 2021)
Today's society needs to organise interreligious and socio-religious dialogues in order manage to work effectively for finding a form of concord between peoples, so that no more unfortunate events such as terrorist attacks and other violent acts occur. One of the solutions is given by the interreligious dialogue carried out worldwide, a dialogue from which the participants, although having different traditions and cultures, can draw points of common interest, so that peace becomes a natural conclusion of the latter.